Potentiality of Exosomal Proteins as Novel Cancer Biomarkers for Liquid Biopsy - Hu, Chunmiao; Jiang, Wei; Lv, Mingjin; Fan, Shuhao; Lu, Yujia; Wu, Qingjun; Pi, Jiang (Frontiers in Immunology, 2022)
Liquid biopsy has been rapidly developed in recent years due to its advantages of non-invasive and real-time sampling in cancer prognosis and diagnosis. Exosomes are nanosized extracellular vesicles secreted by all types of cells and abundantly distributed in all types of body fluid, carrying diverse cargos including proteins, DNA and RNA that transmit regulatory signals to recipient cells. Among the cargos, exosomal proteins have always been used as immunoaffinity binding targets for exosome isolation. Increasing evidences about the function of tumor-derived exosomes and their proteins are found to be massively associated with tumor initiation, progression and metastasis in recent years. Therefore, exosomal proteins and some nucleic acids, such as miRNA, can be used not only as the targets for exosome isolation but also as potential diagnostic markers in cancer research, especially for liquid biopsy. This review will discuss the existing protein-based methods for exosomes isolation and characterization that are more appropriate for clinical use based on current knowledge of the exosomal biogenesis and function. Additionally, the recent studies for the use of exosomal proteins as cancer biomarkers are also discussed and summarized, which might contribute to the development of exosomal proteins as novel diagnostic tools for liquid biopsy.